Zn II and As II CW laser transitions excited by an electron beam - Meyer, J. D., author; Rocca, Jorge J., author; Collins, G. J., author; IEEE, publisher (Colorado State University. Libraries, 1982)
CW laser action was obtained on the 4911.6, 4924.0, 6102.5, and 7588.5 Å transitions of Zn II and on the 6511.7 Å transition of As II using electron beam excitation of He-Zn and He-As mixtures, respectively.